Pelatihan Informasi dan Pengolahan Data (INFOLAHTA) dengan Microsoft Excel bagi Prajurit dan PNS KOREM 052/Wijayakrama Kodam Jaya - Jansen Wiratama; Fenina Adline Twince Tobing; Monika Evelin Johan; Rudi Sutomo; Johan Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Within the KOREM 052/Wijayakrama Kodam Jaya environment, proficient information management and data processing have emerged as important determinants of success. In the contemporary military and civil service, mastery in extracting, analyzing, and interpreting information is indispensable for frontline service members and administrative civil servants. Therefore, this training activity is very relevant and essential in preparing them. Report and Data Processing (INFOLAHTA) addresses this need by equipping participants with the transformative potential of Microsoft Excel, positioned at the intersection of technological advancement and strategic skills. This training, led by Multimedia Nusantara University, facilitates training for soldiers and civil servants in Microsoft Excel to process data and information. The results obtained from the participants, combined with the trainers' expertise and support from KOREM 052/Wijayakrama Kodam Jaya, underscore the transformational impact of INFOLAHTA. Empowered Soldiers and Civil Servants emerge proficient at Excel, ready to perform their roles skillfully and confidently. This Community Outreach activity shows the importance of INFOLAHTA in improving professional competence and fostering a culture of continuous learning and innovation. The ongoing impact of this effort is expected to enrich the insights and capabilities of Soldiers and Civil Servants.